Penerapan Metode Waterfall dalam Perencanaan Sistem Informasi Penjualan Buku berbasis Aplikasi Website (Studi Kasus: Penjual Buku Toko 21 Jombang) - Kusyadi, Irpan; S, Amaranullah Putra; Oktafani, Muhammad Dio; Ardani, Muhammad Rifky Adrian; Syaugi, Muhammad; Yulianti, Yulianti (Program Studi Teknik Informatika Universitas Pamulang, 2022)
Information system is a system that combines human activities and the use of technology to support management and operational activities. Waterfall method is the oldest software development method because it is natural. The Website application itself is a program designed specifically for mobile phones with the Website operating system. In this study, the researcher wrote how to create an Website application information system by applying the waterfall method.